Liquefaction optimization of Crataegus monogyna Jacq - Dulyanska, Y (2024)
The objective of this work was to evaluate the potentiality of Crataegus monogyna Jacq. residues to be liquefied by polyhydric alcohols and the chemical transformations observed in this process with subsequent use to produce polyurethane foams. The variations on liquefaction yield were determined at different temperature, time, material/solvent ratio and granulometry. Results show that liquefaction performed at 180 °C with a 1:10 material/solvent ratio increases along time, reaching a maximum at 60 min. Similarly, liquefactions made during 60 min with a 1:10 material/solvent ratio show that there is an increase in liquefaction yield with the increase in temperature until 180 °C. A higher temperature could increase the liquefaction yield but would lead to a higher energy consumption in the process. There seems to be no significative advantage in increasing material/solvent ratio above 1:7, although the liquefaction yield increases for higher ratios. Granulometry testing shows that the smaller the particle the best is the liquefaction percentage. It was concluded that the best liquefaction yield, of approximately 81%, was obtained with a temperature of 180 °C, for 60 min and particle size <80 mesh for Crataegus monogyna Jacq. This material has good properties to be converted in a liquid mixture that can be used later, on the production of polyurethane foams.